2011
DOI: 10.1155/2011/235873
|View full text |Cite
|
Sign up to set email alerts
|

Conjoined Twins in a Triplet Pregnancy: A Case Report

Abstract: Background. Conjoined twins are a rare complication of monozygotic twinning and are associated with high perinatal mortality. Case. Here we present a case of conjoined twins in a triplet pregnancy diagnosed at 13 of weeks gestation. With the aid of 3D ultrasound and MRI images, the parents were counseled regarding the management options, including continuation of pregnancy, termination of pregnancy, or selective fetocide. They chose selective fetocide of the conjoined twins and went on to deliver the remaining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…A number of unique complications develop in twin pregnancies (Cunningham et al, 2010;Steven G. Gabbe et al, M, Adams, 2007;Shepherd and Smith, 2011;Simpson, 2013;Breathnach and Malone, 2012;Mille et al, 2012;Blickstein andPerlman, 2012 andMorin andLim, 2011). In our study there were 1.4% of both twin deaths, 21.5% of co-twin deaths, 5.6% of discordant twin and 0.7 % of congenital malformation i.e.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…A number of unique complications develop in twin pregnancies (Cunningham et al, 2010;Steven G. Gabbe et al, M, Adams, 2007;Shepherd and Smith, 2011;Simpson, 2013;Breathnach and Malone, 2012;Mille et al, 2012;Blickstein andPerlman, 2012 andMorin andLim, 2011). In our study there were 1.4% of both twin deaths, 21.5% of co-twin deaths, 5.6% of discordant twin and 0.7 % of congenital malformation i.e.…”
Section: Discussionsupporting
confidence: 47%
“…Studies in two referral hospitals of Ethiopia namely St. Paul's Hospital in Addis Ababa and Mekele zonal hospital in Tigray showed low birth weight was identified in 53.5% and 55.9% of twin births respectively. Another study in USA indicated that preterm delivery and low birth weight to occur in 59% and 57% respectively (Gessessew, 2007;Shepherd andSmith, 2011 andKorsak, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…These pregnancies require early and repeated ultrasonographic evaluation, to detect implantation, foetal cardiac function, or ectopic pregnancies [ 19 ]. Given the opportunity, chorionicity can be diagnosed with accuracy, providing the clinicians with valuable information for the following obstetric care of these pregnancies [ 20 , 21 , 22 , 23 ]. Recent data suggest that the rate of monozygotic twinning is increased when using ART, especially when blastocysts are transferred, but the risk for CT has not been evaluated after ART [ 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, early selective termination in dichorionic gestations resulted in term delivery of the healthy triplet [ 7 , 20 ]. This is a strong indication that early (preferably first trimester) and accurate determination of chorionicity, is crucial for the decision of the optimum management in such cases [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are 16 cases of ART-associated CTs including this case report. These cases are summarized in Table 1 [36][37][38][39][40][41][42][43][44][45][46][47][48][49]. Out of the 16 cases of CTs, ten occurred after fresh embryos transfer, four after frozen embryos transfer, and two after ovulation induction (OI) by clomiphene.…”
Section: Maternal Agementioning
confidence: 99%